Neurology training in sub‐Saharan Africa: A survey of people in training from 19 countries. Issue 6 (22nd April 2016) - Mateen, Farrah J.; Clark, Sarah J.; Borzello, Mia; Kabore, Jean; Seidi, Osheik
Abstract : Objective: To provide a comprehensive understanding of neurology training from the sub‐Saharan African perspective. Methods: A 40‐question survey was distributed to attendees of the 7th annual sub‐Saharan African neurology teaching course in Khartoum, Sudan (2015). Themes included the student body, faculty, curriculum, assessment and examinations, technology, and work hours and compensation. Results: Of 19 responding countries, 10 had no formal neurology training programs; Burkina Faso, Cameroon, Republic of the Congo, and Mozambique had an adult neurology program; Ethiopia, Madagascar, Nigeria, Senegal, and South Africa had adult and pediatric neurology programs (training duration range = 3–6 years). There was a median of 2.5 full‐time neurologists on the teaching faculty at the respondents' training institutions (neurologists on‐faculty:in‐country ratio = 0.48), with the lowest ratios in Sudan and Nigeria. Neurology was perceived to be a competitive specialty for entrance in 57% of countries, with 78% of respondents reporting a requisite entrance examination. Ninety‐five percent had access to a personal smartphone, 62% used the Internet more than occasionally, and 60% had access to online neurology journals. The average number of weekly work hours was 51 (range = 40–75), and average monthly salary among those earning income was 1, 191 USD (range = 285–3, 560). Twenty percent of respondents reported paying for training. The most common barriers to neurology postgraduate education were few training programs and lack of training in neurodiagnostic tests. Among 17 reporting countries, there is an estimated average of 0.6 neurologists per million people. Interpretation: Neurology training programs in sub‐Saharan Africa are relatively limited in number and have several unmet needs including a small cadre of faculty and an opportunity to standardize curricula and financing of programs. Ann Neurol 2016;79:871–881